Analisis Persepsi Kebijakan PPN PMSE, Kenaikan PPN dan Harga Produk Terhadap Keputusan Pembelian Netflix - Husna, Qonita Af'idatul; Pahala, Indra; Khairunnisa, Hera (LPPM Universitas Negeri Jakarta, 2025)
This study aims to analyze the effect of the PPN PMSE policy, PPN increase, and product prices on Netflix purchasing decisions in Indonesia. The implementation of PPN on Electronic System Trading (PMSE), which affects the price of digital services, including Netflix, forms the background of this study. The method used is quantitative with multiple linear regression analysis to test the relationship between these variables. The results indicate that perceptions of the PPN PMSE policy and PPN rate increases significantly influence purchasing decisions, while perceptions of product prices also affect consumer decisions. Practically, companies need to provide clear information about the impact of tax policies on product prices so that consumers understand their contribution to national development. Additionally, companies should design more transparent marketing strategies. Further research is recommended to explore other factors influencing digital service purchase decisions and the impact of price and product quality in the context of digital services.